Managing community open spaces in semi-arid region, Katsina Nigeria - Muhammad Gidado, Usman; Maulan, Suhardi; Mohd Yusof, Mohd Johari; Ibrahim, Roziya (UiTM, 2022)
Desertification hurts the agricultural lands and water sources, as well as the community's open spaces. Open spaces are regarded as an integral feature of the landscape in rural communities in semi-arid regions because they host the community's socio-cultural and economic activities. In North-Western Nigeria, the menace of land degradation is a result of desertification. Thus, this makes it necessary for the communities to develop some strategies to manage the open spaces. Therefore, there is a need to ensure an organized and well-managed open space in North-Western Nigeria to accommodate the culture and the ethical values of the communities. An in-depth interview with the community leaders and site observation approaches on community open spaces was conducted to investigate the community’s management strategies (local approaches) for the sustainability of open spaces in hosting the socio-cultural activities in a semi-arid region of North-Western Nigeria and the management strategies. The results were analyzed using ATLAS Ti with the actual analysis done during the writing phase and presented using simple statistical tools. The study revealed the typology and the functions of the community open spaces, and further, explored the stakeholders and management strategies. The study suggests that governments should recognize and support community-based organizations (CBOs) financially and otherwise, to enable them to achieve their goals in managing community open spaces. The result will serve as a guiding document for policymakers, resource planners, and decision-makers. It will also ensure proper order in the use of open spaces by the communities.